ISOLASI DAN KARAKTERISTIK BAKTERI XILANOLITIK YANG BERPOTENSI SEBAGAI BIO-DEKOMPOSER - Setiawan, Rony; Sumardi; Sari, Ayuni Mitra (Cocos Bio, 2024)
Sugarcane (Saccharum officinarum L.) is a plant used for sugar production with waste products in the form of bagasse and sugarcane leaves. Sugarcane pulp and leaves are known t°Contain hemicellulose (xylan) which has the potential to be used as a rough substrate for xylanase-producing microorganisms. The aim of the research was to isolate xylanolytic bacteria from sugar cane plantations and to know the characteristics of xylanolytic bacteria. The research was conducted in December 2022- February 2023. This research was divided into 2 parts, namely experiment and observation. Experimental research in the form of biological characters using Completely Randomized Factorial Design (RALF). The first factor was the pH of the media, namely pH 4, pH 5, and pH 6. The second factor was temperature, using a temperature of 25°C and 45°C. Each treatment was carried out with 3 replications. To determine the characteristics of xylanolytic bacteria, an observational study was carried out by conducting a hypersensitivity test and observing the macroscopic and microscopic morphology of the bacterial colonies. The results showed that the best bacterial pH in producing the enzymatic index was at pH 4 and 25°C. Hypersensitivity test showed that all isolates were pathogenic.